Study on Effective Diffusivity of Sea Cucumbers with Heat Pump Drying - Zhao Haibo; Yang Zhao; Dai Jiaao; Qiao Lingmin; Zhang Lingling (Zhileng xuebao)
The effective diffusivity is an important parameter for mass transfer research on the drying of sea cucumbers. The dependence of the effective diffusivity on temperature has been adopted in current studies, while the effects of moisture content and shrinkage have often been ignored. Therefore, in this paper, a finite element dry model is built and the diffusivity determination method based on the model is applied to study the diffusivity in sea cucumber heat pump drying. The influences of shrinkage during heat pump drying, temperature and moisture content on diffusivity have been studied and analyzed. The results show that the drying shrinkage, temperature, and moisture content affect the effective diffusivity greatly. The effective diffusivities, as determined by considering the effects of shrinkage, temperature and moisture content, are 3.9-14.6% lower than those considering the effects of temperature and moisture content The effective diffusivities determined by considering the effects of shrinkage and temperature are 8.7-14.5% lower than those only considering the effect of temperature. The effective diffusivity increases with both temperature and moisture content. Models considering drying shrinkage and influence of temperature and moisture content on diffusivity can preferably predict moisture content variation in line with the experimental values, with a coefficient of correlation higher than 0.994. The effective diffusivity decreases along the radial direction in the sea cucumber. As drying proceeds from 1 to 15 h, the difference in effective diffusivity between the center and the surface of sea cucumber reduces from 6.4 × 10-10 m2/s to 0.9 × 10-10 m2/s, and the effective diffusivity in the center decreases from 14.6×10-10 m2/s to 8.9×10-10 m2/s.